Acantholytic Acanthoma of the Eyelid: Unusual Presentation. Issue 4 (July 2016) - Mittal, Ruchi; Mahapatra, Samir
Abstract : Acantholytic acanthoma is a benign epidermal tumor with a truncal predisposition and is not previously reported as an eyelid mass. A 63-year-old man, presented with a history of nodular masses of both his eyelid margin and eyelid surface of 3 years duration. Excision biopsy of lesion of eyelid margin was consistent with dermal nevus. Lesions of the eyelid surface displayed prominent acanthosis, acantholysis, and spongiosis. Variable hyperkeratosis and papillomatosis was also noted. There was absence of cytological atypia or mitoses. The microscopic picture was consistent with acantholytic acanthoma. The presence of extensive acantholysis in the present case excluded incidental focal epidermolytic hyperkeratosis and focal acantholytic dyskeratosis. Acantholytic vesiculobullous disorders and numerous acanthotic disorders, which are more common in the eyelid, need exclusion. To the authors' best knowledge, as acantholytic acanthoma of the eyelid is not previously reported, they recommend that it should be included as differential diagnoses of benign epidermal lesions of eyelid. Abstract : Acantholyticacanthoma is a rare benign epidermal tumor characterized by prominent acantholysis and acanthosis. Knowledge of morphological presentation of this rare tumor is essential for correct identification and differentiation of this lesion from other commoner acanthotic and acantholytic disorders of the eyelid.